2018
DOI: 10.1152/ajpheart.00197.2018
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII-dependent late Na+current increases electrical dispersion and arrhythmia in ischemia-reperfusion

Abstract: The mechanisms underlying Ca/calmodulin-dependent protein kinase II (CaMKII)-induced arrhythmias in ischemia-reperfusion (I/R) are not fully understood. We tested the hypothesis that CaMKII increases late Na current ( I) via phosphorylation of Na1.5 at Ser during I/R, thereby increasing arrhythmia susceptibility. To test our hypothesis, we studied isolated, Langendorff-perfused hearts from wild-type (WT) mice and mice expressing Na channel variants Na1.5-Ser571E (S571E) and Na1.5-Ser571A (S571A). WT hearts sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…Consistent with findings of previous studies in both atrial ( 24 ) and ventricular myocytes ( 21 , 23 ), we found that exposing left atrial myocytes to apelin increased the maximal I Na conduction in association with a reversible hyperpolarizing shift in steady-state sodium channel activation combined with AP prolongation. This latter finding can help explain the ability of apelin to increase atrial refractoriness and prolong APDs, as reported previously ( 40 , 41 )), actions which are expected to reduce arrhythmia vulnerability ( 42 ).…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with findings of previous studies in both atrial ( 24 ) and ventricular myocytes ( 21 , 23 ), we found that exposing left atrial myocytes to apelin increased the maximal I Na conduction in association with a reversible hyperpolarizing shift in steady-state sodium channel activation combined with AP prolongation. This latter finding can help explain the ability of apelin to increase atrial refractoriness and prolong APDs, as reported previously ( 40 , 41 )), actions which are expected to reduce arrhythmia vulnerability ( 42 ).…”
Section: Discussionsupporting
confidence: 81%
“…A recent study reported that CaMKIId activation contributes to diastolic Na þ and Ca 2þ overload and impaired diastolic function. 29 Indeed, our western blot analysis showed that CaMKIId autophosphorylation was significantly up-regulated by 308 ± 42% in HCM iPSC-CMs compared with Ctrl iPSC-CMs, which was partially suppressed by I Ca or I NaL blockers ( Figure 6B). To confirm the role of CaMKIId in DD, we sought to over-express (OE) the constitutivelyactive form of CaMKIId T287D in Ctrl iPSC-CMs, and to knockdown (KD) CaMKIId in HCM iPSC-CMs (Supplementary material online, Figure S10A-C).…”
Section: Improve the Viability Of Hypertrophic Cardiomyopathy Inducedmentioning
confidence: 84%
“…Optical mapping of ex vivo heart preparations. Optical mapping techniques were used to measure the electrical impulse propagation in the anterior portion of the isolated heart, as described (39). Briefly, hearts were perfused with oxygenated Tyrode's solution (at 37°C and pH of 7.4) via the aorta using a rolling pump at 2 mL/min.…”
Section: Methodsmentioning
confidence: 99%